Evaluating Tumor‐Infiltrating Lymphocytes in Breast Cancer: The Role of Conventional Ultrasound and Contrast‐Enhanced Ultrasound. (21st July 2022) - Jia, Yingying; Zhu, Yangyang; Li, Ting; Song, XueWen; Duan, Ying; Yang, Dan; Nie, Fang
Abstract : Objectives: Tumor‐infiltrating lymphocytes (TILs) have emerged as an efficient biomarker predicting treatment response and prognosis of breast cancer (BC). This study aimed to evaluate the association between conventional ultrasound and contrast‐enhanced ultrasound (CEUS) imaging features with TIL levels in invasive BC patients. Methods: We retrospectively included 267 women with invasive BC who had undergone conventional ultrasound and CEUS. Patients were divided into low (≤10%) and high (>10%) TIL groups. Conventional ultrasound and CEUS features were analyzed by two sonographers. The associations between the TIL levels and imaging features were evaluated. Results: Of the 267 patients, 122 with high TILs and 145 with low TIL levels. High TIL tumors were more likely to have a circumscribed margin, oval or round shape, and enhanced posterior echoes on ultrasonography ( p < 0.05). In contrast, low TIL tumors were more likely to have an irregular shape, un‐circumscribed, indistinct and spiculated margin ( p < 0.05). In CEUS, high TIL tumors showed a more regular shape, clearer margin, more homogeneous enhancement and higher peak intensity (PI) value ( p < 0.05). Logistic analysis indicated that shape, posterior features, PI, and enhanced homogeneity were independent predictors for high TIL tumors. The model combined the four independent predictors have a moderate performance in predicting high TIL tumors with AUC 0.79, sensitivity 0.72, and specificity 0.78. Conclusions: Conventional ultrasound and CEUS features were associated with TIL levels in invasive BC. Consequently, the results suggested that preoperative conventional ultrasound and CEUS may be a useful noninvasive imaging biomarker for individualized treatment decisions. Abstract : Access the CME test here and search by article title.